Intellectual Structure Of Ongoing Studies on Business Schools - Isabel Cristina Scafuto; Fernando Serra; Luiz Guerrazzi; Emerson Maccari (BBR: Brazilian Business Review)
We examined the extant research on Business Schools (B-Schools) in an attempt to understand the intellectual structural influences in mainstream research, as well as the evolution and trends in research. Through a bibliometric study of co-citation and bibliographic coupling, supported by factor and network analyses of a sample of 493 articles, we examined 76 selected articles and their references. The results indicate that critiques of B-Schools influenced mainstream works. We found three primary sources of criticism at the intellectual level: Theory and Practice Gap, Social Relevance, and Curricula and Practice. The mainstream works identified six different topics: B-School Relevance, Teaching Relevance, Relevance to Practice, Curricula Relevance, B-School Evolution, and Influence, and Reputation. The longitudinal analysis identified four trends: Relevance to Practice, Social Relevance, Academic-Practitioner Divide, and Teaching Relevance. Through our bibliometric research, we contribute to the B-Schools research in two ways. It enabled the identification of works and themes that influenced reflections on B-Schools, as they influenced the ongoing research, and consequently, the research trends. Furthermore, the results serve as possible orientations for B-School managers.